Diverse populations of intrinsic cholinergic interneurons in the mouse olfactory bulb - Krosnowski, Kurt (2012)
Cholinergic activities affect olfactory bulb (OB) information processing and associated learning and memory. However, the presence of intrinsic cholinergic interneurons in the OB remains controversial. As a result, morphological and functional properties of these cells are largely undetermined. We characterized cholinergic interneurons using transgenic mice that selectively mark choline acetyltransferase (ChAT)-expressing cells and immunolabeling. We found a significant number of intrinsic cholinergic interneurons in the OB. These interneurons reside primarily in the glomerular layer (GL) and external plexiform layer (EPL) and exhibit diverse distribution patterns of nerve processes, indicating functional heterogeneity. Further, we found these neurons express ChAT and vesicular acetylcholine transporter (VAChT), but do not immunoreact to glutamatergic, GABAergic or dopaminergic markers and are distinct from calretinin-expressing interneurons. Interestingly, the cholinergic population partially overlaps with the calbindin D28K-expressing interneuron population, revealing the neurotransmitter identity of this sub-population. Additionally, we quantitatively determined the density of VAChT labeled cholinergic nerve fibers in various layers of the OB, as well as the intensity of VAChT immunoreactivity within the GL, suggesting primary sites of cholinergic actions. Taken together, our results provide clear evidence showing the presence of a significant number of cholinergic interneurons and that these morphologically and distributionally diverse interneurons make up complex local cholinergic networks in the OB. Thus, our results suggest that olfactory information processing is modulated by dual cholinergic systems of local interneuron networks and centrifugal projections.